Spectators` “BlackLists” and Recovery of Damages by Football Clubs from Spectators for the Violation of the Rules of Conduct: A Russian Experience - Vasilyev, Ilya; Hong Qiang, Yue; Kashaeva, Anastasia; Izmalkova, Margarita; Khalatova, Raisa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
he right of football clubs to establish local bans (the so-called “blacklists”) depends on a number of reasons. A local ban on visiting football matches can act as a measure to combat the unlawful behaviour of viewers, thus complementing the administrative responsibility of the spectators. In Russian law it is not possible to impose a ban on the sale of tickets to football matches by football clubs. The current wording of the rules of spectators’ behaviour during official sporting events does not, by default, allow supporter identity checks when entering the stadium. That also complicates the identification of spectators for being on the “blacklist”. The practice of civil suits brought by football clubs against supporters, as one of the few legal tools to influence supporters, is currently not widespread. As a result, there are no uniform approaches to resolve these disputes: the courts motivate refusals by various arguments, the validity of which can be reasonably criticised.